2005
DOI: 10.1099/mic.0.28132-0
|View full text |Cite
|
Sign up to set email alerts
|

Two glutathione peroxidases in the fungal pathogen Cryptococcus neoformans are expressed in the presence of specific substrates

Abstract: Glutathione peroxidases catalyse the reduction of peroxides by reduced glutathione. To determine if these enzymes are important for resistance to oxidative stress and evasion of the innate immune system by the fungal pathogen Cryptococcus neoformans, two glutathione peroxidase homologues, which share 38 % identity, were identified and investigated. In this study, these peroxidases, Gpx1 and Gpx2, their localization, their contribution to total glutathione peroxidase activity, and their importance to the oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 29 publications
1
37
1
Order By: Relevance
“…Missall et al demonstrated that TSA1, one of three C. neoformans thiol peroxidase genes, and the glutathione peroxidase genes GPX1 and GPX2 contribute to protection against oxidative stress in vitro (36,37). In addition, TSA1 has contributed to virulence in a murine model of cryptococcosis (36,37). The results of these studies suggest that the C. neoformans antioxidant system is composed of several functionally overlapping and compensatory components that provide protection against endogenous and exogenous oxidative stresses.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Missall et al demonstrated that TSA1, one of three C. neoformans thiol peroxidase genes, and the glutathione peroxidase genes GPX1 and GPX2 contribute to protection against oxidative stress in vitro (36,37). In addition, TSA1 has contributed to virulence in a murine model of cryptococcosis (36,37). The results of these studies suggest that the C. neoformans antioxidant system is composed of several functionally overlapping and compensatory components that provide protection against endogenous and exogenous oxidative stresses.…”
mentioning
confidence: 60%
“…This resistance can be accomplished in a number of different ways, including the production of factors that prevent host effector cells from eliciting an oxidative burst, the possession of nonenzymatic antioxidants (such as melanin and mannitol), and the utilization of enzymatic antioxidants (such as catalases, superoxide dismutases, and various peroxidases) to degrade ROS. The complexity of the antioxidant defense system is illustrated by the retained ability of many C. neoformans mutants with antioxidant defense defects to cause morbidity and mortality in a manner undistinguishable from that of wild-type strains (20,36). C. neoformans can colonize the lung, which suggests that it possesses adequate antioxidant defenses to overcome the oxygen-dependent killing mechanisms of alveolar macrophages (14,15,29,30,42,50,52) and other host phagocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione reductase is necessary for reducing the glutathione disulfide, which is formed as a by-product of glutathione peroxidases or glutaredoxins in the presence of reactive oxygen or nitrogen species. The importance of the glutathione peroxidases in C. neoformans to the oxidative stress response has recently been described (32), but enzymes of the glutathione system have yet to be shown to be important for the nitrosative stress response in any organism. We find that mutants deficient in Glr1 are sensitive to nitric oxide stress, but not peroxide stress, revealing a specificity between oxidative and nitrosative stress resistance mechanisms in C. neoformans.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular pathogenicity of C. neoformans is most likely facilitated by stress resistance mechanisms, including a number of antioxidant proteins and pathways involved in the detoxification of ROS and RNS. Specifically, these include the synthesis of mannitol, a free radical scavenger (9,20); the small protein flavohemoglobin denitrosylase (Fhb1), which is essential for resistance of C. neoformans to nitrosative stress (10,14,32); and the glutathione and thioredoxin antioxidant systems, which are both important for stress resistance and virulence (42,43,45).…”
mentioning
confidence: 99%